1872 Mich. Comp. Laws. ch. 64, § 4. - (:unkn) unknown (General Publisher, 1872)
No person or persons shall at any time kill or attempt to kill any wild duck, or other wild fowl, with or by means of a swivel or punt gun, or rob or destroy the nests of any wild ducks or wild geese, or in any manner kill or molest the same whilst they are sitting at night on their nesting places.
--
Keywords: HUNTING REGULATION